1996
DOI: 10.1183/09031936.96.09051024
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research into the pathogenesis of cobalt/hard metal lung disease

Abstract: In recent years clinical, epidemiological and experimental evidence has accumulated indicating that cobalt metal particles, when inhaled in association with other agents such as metallic carbides (hard metals) or diamond dust, may produce an interstitial lung disease termed "hard metal disease" or "cobalt lung". This article summarizes the progress accomplished in our two laboratories to understand the pathogenesis of this disease. Gaps and weaknesses in our current knowledge have also been highlighted in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
4

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 25 publications
1
63
0
4
Order By: Relevance
“…If Co particles in the presence of WC particles cause HMD via generation of ROS [4][5][6] , then our characterization of airborne particles may help to explain the inconsistent findings of epidemiological studies, e.g., between Meyer-Bisch et al 1) and Sprince et al 2) ; only Sprince et al 2) showed a higher risk in the later stages of the CTC manufacturing process. We observed that airborne particles potentially available for inhalation in spray drying and all subsequent work areas were a mixture of elemental tungsten and elemental Co particles and/or multi-constituent W/Co particles (ostensibly WC/Co particles, but the relative carbon contribution of the collection substrate and metal carbides is unknown).…”
Section: Airborne Particlesmentioning
confidence: 80%
See 1 more Smart Citation
“…If Co particles in the presence of WC particles cause HMD via generation of ROS [4][5][6] , then our characterization of airborne particles may help to explain the inconsistent findings of epidemiological studies, e.g., between Meyer-Bisch et al 1) and Sprince et al 2) ; only Sprince et al 2) showed a higher risk in the later stages of the CTC manufacturing process. We observed that airborne particles potentially available for inhalation in spray drying and all subsequent work areas were a mixture of elemental tungsten and elemental Co particles and/or multi-constituent W/Co particles (ostensibly WC/Co particles, but the relative carbon contribution of the collection substrate and metal carbides is unknown).…”
Section: Airborne Particlesmentioning
confidence: 80%
“…It is interesting to speculate on the potential implications of our results, which suggest more intimate contact between Co and WC in post-screened particles relative to pre-spray dried particles, for generation of ROS and risk of HMD. It has been reported that the Co constituent of pre-sintered WC/Co powder is oxidized in vitro, releasing electrons that are transferred to the surface of WC where atmospheric oxygen is reduced, resulting in generation of ROS [4][5][6] . In pre-sintered powder, metallic Co and WC may be held in contact by weak electrostatic bonds or by van der Waals forces.…”
Section: Airborne Particlesmentioning
confidence: 99%
“…Using powder concentrations of 22.5 mg/ml (which is high relative to observed mass concentrations in Table 1) and an electron spin resonance technique, Lison et al ( , 1996 proposed the following precise mechanism for HMD: when both cobalt metal (which is thermodynamically able to reduce ambient oxygen) particles and tungsten carbide (a good electron conductor) particles are associated, electrons provided by the cobalt metal are easily transferred to the surface of the carbide particles, where reduction of oxygen can occur at an increased rate, resulting in the generation of free radicals. Analogous results have been reported for genotoxicity studies (Anard et al, 1997;Van Goethem et al, 1997;Lison et al, 2001;De Boeck et al, 2003a, b;Mateuca et al, 2005): cobalt associated with tungsten carbide particles (mechanical mixture or pre-sintered hard metal powder) produce more free radicals and DNA strand breaks than pure cobalt or tungsten carbide powder alone.…”
Section: Hard Metal Disease and Lung Cancermentioning
confidence: 99%
“…Using in vitro and in vivo models, researchers investigating the mechanistic basis of HMD (Lasfargues et al, 1992;Lison and Lauwerys, 1990, 1994, 1995Lison et al, , 1996Zanetti and Fubini, 1997;Keane et al, 2002;Mutti and Corradi, 2006;Moriyama et al, 2007) observed that a mechanical mixture of pure cobalt and tungsten carbide powders prepared in the laboratory and pre-sintered hard metal powder (mixture of cobalt, tungsten, and carbon) were more toxic than pure tungsten carbide or pure cobalt powder alone; the increased toxicity of the powder mixtures was attributed to the generation of free radicals via a localized reaction, that is, on a particle surface or between particle surfaces in contact, and not from the reaction of a solubilized component at the solid surface. Using powder concentrations of 22.5 mg/ml (which is high relative to observed mass concentrations in Table 1) and an electron spin resonance technique, Lison et al ( , 1996 proposed the following precise mechanism for HMD: when both cobalt metal (which is thermodynamically able to reduce ambient oxygen) particles and tungsten carbide (a good electron conductor) particles are associated, electrons provided by the cobalt metal are easily transferred to the surface of the carbide particles, where reduction of oxygen can occur at an increased rate, resulting in the generation of free radicals.…”
Section: Hard Metal Disease and Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation